Analisis Teknis dan Ekonomi Usaha Pemotongan Sapi Berdasarkan Bobot Badan Hidup, Bobot Karkas, Biaya Produksi, dan Hasil Penjualan - Putri Wiranti; Mudawamah Mudawamah (Dinasti Research, 2026)
This study aims to analyze the technical and economic analysis of the cattle slaughter business at PT. Rumah Potong Hewan Surabaya Perseroda. The technical analysis is focused on measuring live weight, carcass weight, and carcass percentage (yield). This research method uses a case study conducted on a sample of beef cattle carried out at PT. Rumah Potong Hewan Surabaya Perseroda on January 15, 2026. Data analysis uses variables of carcass percentage, total production costs, total revenue, profit, and ratio. The results of the study show that cattle with a live weight of 447 kg produce a carcass of 195 kg, with a carcass percentage of 43.62%. From an economic perspective, this business incurs a total production cost of IDR 24,638,000 with a total revenue of IDR 26,167,750, resulting in a net profit of IDR 1,529,750 per cow. The R/C Ratio value obtained is 1.06 which indicates that the cattle slaughter business is feasible and profitable (R/C>1). Optimizing the utilization of by-products has been proven to provide a significant contribution to total business income.